Applying shariah stock screening methodologies for 20 blue chips companies on KOSPI : a proposal to adopt stock screening process - Yu, Hyunil (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
The rapid growth of the Islamic finance industry has gained much attention, not only from Muslim majority countries, but from the Muslim minority countries as well, including South Korea. This rapid growth has led Muslims to invest their wealth in various financial instruments such as shares, bonds, and unit trusts etc., in accordance to Islamic principles. Shariah screening methodologies have been established by world index providers such as Dow Jones or securities regulators at the national level. This was successfully achieved by the aid of eminent Shariah scholars under Shariah consultancy firms. The Korean government have shown great interest in Islamic finance, predominantly, the Islamic capital market because of the diversification opportunities from sources of funding of foreign capital. The primary objective of this paper was to examine Shariah compliant Korean companies listed in KOSPI through the use of different Shariah screening methodologies. This study seeks to find the most suitable Shariah screening methodology in terms of numbers of Shariah compliant shares in Korean equity markets. The sample size comprises of twenty Korean blue chip stocks based on the largest market capitalization on the 27th of February 2015. Data were analyzed using four Shariah stock screening methodologies which are DJIM, FTSE, S&P, and the SAC of SC. The analysis consists of sector screening and financial ratio screening. The findings suggest that 6 companies from the samples are permissible to invest in under DJIM and S&P, 8 companies are qualified by FTSE criteria, and the SAC of SC exhibited the highest number from among the other methodologies, showing 11 companies that are Shariah compliant from the samples of 20 Korean companies. Korean companies' core business consists of 40% of activities deemed prohibited in Islam. This is the primary reason for the non-Shariah compliancy of Korean companies. Furthermore, this study has found the recommendable Shariah screening methodology for the Korean stock market in order to attract more Muslim investors.